GAMBARAN PERENCANAAN KEHAMILAN PADA IBU RUMAH TANGGA HIV POSITIF DI KOTA SEMARANG - Susilawati, Dwi; Shaluhiyah, Zahroh; BM, Syamsulhuda (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2019)
The high number of cases of HIV AIDS in housewives in Semarang City is not only a threat to the safety of the lives of mothers, their babies conceived are at risk of contracting the HIV virus because of transmission from mother to baby. In the second prong of the Prevention of Mother to Child Transmission (PMTCT), prevention of unplanned pregnancies in mothers with HIV is necessary. This study aims to describe pregnancy planning in HIV positive housewives in Semarang City. This study uses a qualitative method. The research subjects were 5 people taken by purposive sampling method and data collection techniques through in-depth interviews. The results showed that careful planning was carried out by subjects who had HIV positive husbands. Condom use was consistently carried out by subjects who had HIV positive husbands and released condoms after fulfilling eligible requirements for the pregnancy. Subjects with high risk aged feel vulnerable to pregnancy, this causes the desire to have fewer children. In planning a pregnancy, most subjects had a CD4 cell count> 350 cells / mm3, almost all subjects had an undetectable viral load, and all subjects had taken ARV regularly for more than 6 months. The actions taken by subjects who did not meet the eligible requirements for the pregnancy included maintaining a diet, adequate rest, taking ARVs regularly, consuming milk for pregnancy preparation, and consulting with a doctor.